IMPLEMENTASI MANAJEMEN MUTU TERPADU DI SEKOLAH TINGGI TEKHNOLOGI SINAR HUSNI MEDAN - Syukri, Makmur; Arianto, Arianto; Annisa, Annisa; S, Aziza (Jurnal Sabilarrasyad, 2019)
The outcome assessment approach emphasizes the evaluation of graduates of educational organizations through student achievement, gradiation and employment. The open approach is an integrated quality assurance system in educational organizations and approaches that emphasize input, process and output. Improving the quality of education also considers the need to fulfill national quality standards. The Content Standards at STT Sinar Husni Medan in general have been well met, this shows STT Sinar Husni Medan always improve the quality of education in a sustainable manner based on the principles of Integrated Education Quality Management. The Targets and Strategies of Achievement of the Sinar Husni Informatics Engineering Study Program until 2020. To get better accreditation scores than before. This can of course be achieved through updating the learning competencies of each course and also supported by practical activities in the field, which adjusted to the needs of stakeholders. Thus each alumni does not need to wait too long to get a job.